Effects of Calcium and Pressure Treatment on Thermal Gelation of Soybean Protein - Speroni Aguirre, Francisco José (2010)
The effect of calcium and high-pressure (HP) treatment on the heat gelation of soybean proteins was investigated. In the presence of calcium (2 to 25 mM), the gelation of dispersions of soybean protein isolate (SPI), a β-conglycinin-enriched fraction (7SEF), and a glycinin-enriched fraction (11SEF) started with protein having a lower degree of denaturation. The gels from these dispersions had greater stiffness than the samples without added calcium. HP treatment had different effects on heat-induced gelation depending on the presence of calcium and on the nature of the proteins. In the absence of calcium, gels with low stiffness were formed after HP treatment, compared with untreated samples, and regardless of the sample type (SPI, 7SEF, 11SEF). In the presence of calcium, gel stiffness was increased after HP treatment of dispersions containing β-conglycinin (SPI and 7SEF), while the opposite effect was observed for 11SEF. In the presence of calcium, HP treatment promoted a greater contribution of hydrophobic interactions in SPI and 7SEF. In the dispersions containing β-conglycinin, these conditions also promoted the appearance of a heterogeneous distribution of molecular sizes, fromenormous aggregates to dissociated species. Our results suggest that, in the presence of calcium, HP treatment has an opposite effect on the ability of glycinin and β-conglycinin to participate in the formation of a 3-dimensional network upon heating.